Analysis of the 4Ps in Social Movements and its Parallel in Professional World. - Singh, Dr. Sudhir; Suri, Sunil (International Journal of Scientific Research and Management (IJSRM), 2024)
The 4Ps in marketing (Product, promotion, packaging and prices) find compelling parallel in the four Ps of social movements (philosophy, practical, profit and personal). The alignment is evident in the progression from a strong movement to a particular philosophy to potential deviations in pursuit of profitability. These parallels extend to the trajectories of startups and political entities, underscoring the importance of prioritizing values, principles and philosophy along side financial success.